2014
DOI: 10.1007/s11934-014-0439-9
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation and Management of Persistent Nocturia

Abstract: Nocturia, or waking at night to void, is a common symptom that leads to substantial morbidity. Men and women are both affected across a wide age range, such that the objective evaluation of nocturia remains a challenge, due largely to its multifactorial etiology. While for some patients, nocturia is caused by common structural conditions such as prostatic obstruction, for others it is due to a complex interplay between multiple underlying systemic diseases. For this reason, persistent nocturia merits particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In contrast to the antidiuretic drug desmopressin, the aim of diuretics for nocturia is to induce diuresis before sleep and to shift the polyuric phase from night‐time (sleep) to daytime . This approach may be suitable for patients with nocturia when the underlying cause is unknown, although the overall evidence supporting the use of diuretic therapy is low. Timing of diuretic therapy is important.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the antidiuretic drug desmopressin, the aim of diuretics for nocturia is to induce diuresis before sleep and to shift the polyuric phase from night‐time (sleep) to daytime . This approach may be suitable for patients with nocturia when the underlying cause is unknown, although the overall evidence supporting the use of diuretic therapy is low. Timing of diuretic therapy is important.…”
Section: Resultsmentioning
confidence: 99%
“…33 Use of a screening tool, such as the recently published TANGO(Targetingtheindividual'sAetiologytoGuideOutcomes), 57,58 can also potentially aid in the identification and assessment of nonlowerurinarytractcomorbiditiesassociatedwithnocturia.FVCscan be supplemented by bladder diaries, which are especially useful in compliant patients over longer stretches of time and provide an opportunity for patients to add important qualitative details about or associated with their symptoms. 59 FVCsorbladderdiariesshouldbe completed for a minimum of 3 days, and it is important that the need foraccuracyisexplainedtothepatientbeforeaskingthemtocomplete it. 60,61 These self-monitoring approaches also aim to reflect and educatepatientsonthecorrectuseortimingoffluidintakeinmanaging nocturia.…”
Section: Clinical Presentation and Evaluationmentioning
confidence: 99%
“…It can develop for many different reasons including lifestyle factors, heart failure, diabetes insipidus or mellitus, decreased vasopressin levels, venous insufficiency, or obstructive sleep apnea [8]. Interventions directed to reduce nocturnal urinary output include evening fluid restriction, leg elevation during daytime, timed diuretics, and antidiuretic treatment with desmopressin [9,10]. In fact, one study has shown that nocturnal polyuria (NP) was the most common contributor to nocturia [11].…”
Section: Introductionmentioning
confidence: 99%
“…Treatments to improve FBC include anticholinergics in patients with detrusor over activity and symptoms of overactive bladder (OAB), whereas recently introduced treatment for OAB – beta‐3‐agonist – stimulates beta‐3 receptors, causing smooth muscle relaxation in the bladder and α‐blockers or 5α‐reductase inhibitors in the case of BPE. Therapeutic measures directed to reduce nocturnal urinary output include evening fluid restriction, leg elevation during daytime, timed diuretics and antidiuretic treatment with desmopressin . Despite this knowledge, management of nocturia patients remains to be challenging because unambiguous definitions of NP and reduced FBC are lacking, and there is little evidence with reference to the effect of all possible combinations of treatment modalities in case of a combined aetiology of nocturia …”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic measures directed to reduce nocturnal urinary output include evening fluid restriction, leg elevation during daytime, timed diuretics and antidiuretic treatment with desmopressin. 3,4 Despite this knowledge, management of nocturia patients remains to be challenging because unambiguous definitions of NP and reduced FBC are lacking, and there is little evidence with reference to the effect of all possible combinations of treatment modalities in case of a combined aetiology of nocturia. 2,3,5,6 Therefore, the aim of this study was to determine which combination of parameters derived from FVCs could discriminate patients with nocturia from those without nocturia, in addition to determining the modifiable factors to minimise nocturia.…”
Section: Introductionmentioning
confidence: 99%